The Analysis of Potential and Contribution Tax of Minerals Non-Metallic and Rocks in Kuantan Singingi Regency - Ekwarso, Hendro; ', Erianto; ', Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted in Kuantan Singingi Regency in 2013. The research aims to determine the potential contribution of tax revenue and non-metallic minerals and rocks as well as the efforts made and the obstacles in tax revenue non-metallic minerals and rocks in Kuantan Singingi Regency. The research uses secondary data obtained from the Department of Revenue Kuantan Singingi Regency, the Department of Energy and Mineral Resources Kuantan Singingi Regency, Department of Highways, the Central Statistics Agency (BPS) Kuantan Singingi Regency and Riau Province. Primary data were obtained directly from the location of the research and research resources that generatet ax non-metallic minerals and rocks in Kuantan Singing Regency. The population in this study are all companies that have permit sretrieval non-metallic minerals and rocks as many as 12 companies. While the sample used in this study were all members of the population, but at the time of the study, only 8 companies that perform operation and have a permit. Engineering data was collected by conducting interviews and question and answer directly to the owner of the company and authorized personel at the Department of Energy and Mineral Resources, Department of Revenue, Department of Highways Kuantan Singingi Regency. This study analyzed using quantitative descriptive analysis method. Based on the survey results revealed that the potential tax revenue non-metallic minerals and rocks in Kuantan Singingi Regency large enough, based on the results of the studys how ed that the average potential tax above its target, while the contribution to the Revenue Kuantan Singingi Regency relatively veryless. Efforts tax revenue is not included in the group primed and in effective. The factors that cause the tax doesn’t meet the target lies in the lack of supervision, failure to fully tax payer data, and the low level of public awarenessin paying taxes.Keywords: Potential tax, tax contributions, efforts and obstacles tax revenue receipts.